Design, Synthesis, and Evaluation of Acrylamide Derivatives as Direct NLRP3 Inflammasome Inhibitors. (17th March 2016) - Cocco, Mattia; Miglio, Gianluca; Giorgis, Marta; Garella, Davide; Marini, Elisabetta; Costale, Annalisa; Regazzoni, Luca; Vistoli, Giulio; Orioli, Marica; Massulaha‐Ahmed, Raïhane; Détraz‐Durieux, Isabelle; Groslambert, Marine; et al.
Abstract: NLRP3 inflammasome plays a key role in the intracellular activation of caspase‐1, processing of pro‐inflammatory interleukin‐1β (IL‐1β), and pyroptotic cell death cascade. The overactivation of NLRP3 is implicated in the pathogenesis of autoinflammatory diseases, known as cryopyrin‐associated periodic syndromes (CAPS), and in the progression of several diseases, such as atherosclerosis, type‐2 diabetes, gout, and Alzheimer's disease. In this study, the synthesis of acrylamide derivatives and their pharmaco‐toxicological evaluation as potential inhibitors of NLRP3‐dependent events was undertaken. Five hits were identified and evaluated for their efficiency in inhibiting IL‐1β release from different macrophage subtypes, including CAPS mutant macrophages. The most attractive hits were tested for their ability to inhibit NLRP3 ATPase activity on human recombinant NLRP3. This screening allowed the identification of14, 2‐(2‐chlorobenzyl)‐ N ‐(4‐sulfamoylphenethyl)acrylamide, which was able to concentration‐dependently inhibit NLRP3 ATPase with an IC50 value of 74 μm . The putative binding pose of14 in the ATPase domain of NLRP3 was also proposed. Abstract : CAPS block is on ! Cryopyrin‐associated periodic syndromes (CAPS) are rare genetic diseases caused by gain‐of‐function mutations in NLRP3. Overactivation of the NLRP3 inflammasome is also involved in other metabolic diseases. Herein, a series of acrylamides that inhibit NLRP3‐dependent pyroptosis and IL‐1β release from CAPS‐mutant macrophages are reported. Direct inhibition of NLRP3 ATPase in human isolated NLRP3 has emerged as a potential target for this compound class.